Electrode kinetics in the "capacitive mixing" and "battery mixing" techniques for energy production from salinity differences. (10th September 2015) - Marino, M.; Misuri, L.; Ruffo, R.; Brogioli, D.
Abstract : Highlights: CapMix is a technique for producing energy from solution of different salinities CapMix is based on capture ions from the dilute and release in concentrated solution We compare two classes of materials: activated carbon and battery-like We find that the electrochemical kinetics is in favour of the activated carbons The cell voltage rise is higher in battery-like materials Abstract: The "accumulator mixing" technique, including the capacitive and the battery mixing, is a new developing technology for harvesting the salinity gradient energy, in particular of NaCl solutions, e.g. sea and river water. It is based on a couple of electrodes in a vessel, in which two solutions of different salinity are alternately fluxed. A current flows through the electrodes and its direction is cyclically inverted. Due to the variation of the electrode potentials induced by the salinity change, the charge is extracted from the cell at a higher voltage than applied during the charging phase: this results in a production of energy at the expenses of the salinity difference. We focus on two kinds of electrode materials: chemically modified activated carbon and battery-like electrodes performing redox reactions, with a cycle operated at constant current. We test them with feed solutions at 20 and 500 mM of NaCl. We show that the CAPMIX power production can be easily predicted from the information obtained by galvanostatic cycles performed at constant concentration; indeed, the periodic salinity changes do not significantly affect the overvoltage observed during the parts of the "accumulator mixing" cycle that takes place at constant salinity. The kinetics of the electrodes in the "accumulator mixing" cycle can thus be easily related to the results of classical electrochemical measurements, such as the impedance spectroscopy. In particular, we show that the most relevant parameter that determines the power production of the cell is the real part of the impedance, measured at the frequency of the CAPMIX cycles, i.e. in the range 2–20 mHz mainly dominated by the so-called "diffusion impedance", and the difference between the capacitance in the two feed solutions.